Brain volume decrease in patients with multiple sclerosis investigated by 3T magnetic resonance imaging scanner: A 4‐year observation study. (14th March 2019) - Nakayama, Takahiro; Sasaki, Takuya; Kitamura, Mizuki; Imafuku, Ichiro
Abstract: Objectives: For patients with multiple sclerosis (MS) with a high recurrence rate, treatment with disease‐modifying drugs from the early stage is recommended. Although a decrease in brain volume has been reported in such patients, long‐term and comparison studies with control participants have not been carried out in Japan. Methods: Before this study, we built a cross‐sectional brain image database of control participants. Among 73 patients with MS treated at Yokohama Rosai Hospital from April 2005 to April 2018, 34 MS patients who had been examined by 3T magnetic resonance scanner over a period of 4 years were enrolled in this study. We calculated the total intracranial volume of each patient, and the total brain volume, and gray and white matter volumes were adjusted by the total intracranial volume. We also examined the age, sex, disease‐modifying drugs and type of MS. Results: The brain volume of mild MS patients decreased with age at the same rate as that of control participants. However, the brain volume of all patients treated with fingolimod decreased faster than that of control participants. In some patients treated with interferon, the brain volume decreased faster than that of control participants. The brain volume of mild MS patients did not decrease more than that of control participants. Conclusions: We could not determine the effect of fingolimod on brain volume decrease, because all patients treated with fingolimod were initially treated with interferon during the study period. The early administration of disease‐modifying drugs is recommended from the perspective of minimizing decreases in brain volume.